2005
DOI: 10.1186/bf03352571
|View full text |Cite
|
Sign up to set email alerts
|

The September 5, 2004 off the Kii Peninsula earthquakes as a composition of bending and collision

Abstract: The 2004 off the Kii Peninsula earthquakes ruptured the subducting Philippine Sea plate near the axis of the Nankai Trough. A series of major events (the fore-and mainshocks with M w >7) showed very peculiar rupture characteristics. The depth extent of the foreshock is around 12-23 km below the sea surface; in contrast, that of the mainshock is around 7-17 km, shallower and closer to the upper surface of the plate than the foreshock. The focal mechanism of the foreshock is almost pure reverse faulting, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Taking into consideration these observations, the stress field in the PHS plate in our study area is clearly anomalous. One possible explanation is that the stress field has been disturbed by collision at the Izu Peninsula east of our study area (e.g., Obana et al 2004;Seno 2005;Miyoshi and Ishibashi 2005), but the large difference in orientation of the axes of compressional stress are not well explained by this model. This question requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Taking into consideration these observations, the stress field in the PHS plate in our study area is clearly anomalous. One possible explanation is that the stress field has been disturbed by collision at the Izu Peninsula east of our study area (e.g., Obana et al 2004;Seno 2005;Miyoshi and Ishibashi 2005), but the large difference in orientation of the axes of compressional stress are not well explained by this model. This question requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…Accordingly, we would have expected a similar stress field in the PHS plate below southeast of the Kii peninsula, too. Bending of the plate due to subduction may also affect the stress field within the PHS plate (e.g., Seno 2005;Miyoshi and Ishibashi, 2005), in which compressional and tensional stress perpendicular to the trough axis dominate in the lower and upper parts, respectively, within the lithosphere. However, these mechanisms could not explain the observed direction of compressive stress oriented perpendicular to the direction of plate convergence.…”
Section: Discussionmentioning
confidence: 99%
“…9(a). Microearthquake activity is low in the rupture area of the Tonankai earthquake, whereas it is higher in trench-outer rise region (Seno, 2005;Sakai et al, 2005, see the top of Fig. 9(a)).…”
Section: Discussionmentioning
confidence: 98%
“…These observations revealed that, in recent years, earthquake activities along the Nankai Trough have mostly occurred in the oceanic crust or upper mantle of the subducting PSP (Obana et al 2004Obana and Kodaira 2009;Mochizuki et al 2010;Akuhara et al 2013;Nakano et al 2013Nakano et al , 2014Nakano et al , 2015Akuhara and Mochizuki 2014). The most recent notable events during this time have been the 2004 M JMA 7.1, 7.4, and 6.5 earthquakes off the Kii Peninsula, which occurred in the subducting plate (e.g., Sakai et al 2005;Seno 2005). …”
Section: Introductionmentioning
confidence: 99%